1993
DOI: 10.1139/f93-069
|View full text |Cite
|
Sign up to set email alerts
|

Smolt-to-AduIt Survival Patterns of Sockeye Salmon (Oncorhynchus nerka): Effects of Smolt Length and Geographic Latitude when Entering the Sea

Abstract: Koenings, ). P., H. ). Geiger, and 1. 1. Hasbrouck. 1993. Smolt-to-adult survival patterns of sockeye salmon (Oncorhynshus nerka): effects of smolt length and geographic latitude when entering the sea. Can. 1. Fish. Aquat. Sci. 50: 600-61 1. Variations in smolt-to-adult survival (SAS) of sockeye salmon (Oncorhynchus nerka) relative to smolt length and age and latitude of the nursery Bake outlet were explored for six stocks in Canada, Russia, and Alaska (W. E. Ricker. 1962. ). Fish. Res. Board Can. 19: 537-560… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
92
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 15 publications
5
92
0
Order By: Relevance
“…The release of larger fry may have weakened the effects of size at release within these regions. Koenings et al (1993) reported that the survival of sockeye salmon is strongly linked to smolt size among populations, but the relationship is not a continuous linear function across all smolt lengths, reaching a plateau and even decreasing after a certain smolt size (about 100 mm). If this is true for chum salmon, it may explain our results showing no relationship between the size at release and return rates in WP-HP chum.…”
Section: Variability In Return Rates For the Wp And Hp Chum Salmonmentioning
confidence: 99%
“…The release of larger fry may have weakened the effects of size at release within these regions. Koenings et al (1993) reported that the survival of sockeye salmon is strongly linked to smolt size among populations, but the relationship is not a continuous linear function across all smolt lengths, reaching a plateau and even decreasing after a certain smolt size (about 100 mm). If this is true for chum salmon, it may explain our results showing no relationship between the size at release and return rates in WP-HP chum.…”
Section: Variability In Return Rates For the Wp And Hp Chum Salmonmentioning
confidence: 99%
“…Regarding the fish, McGurk (1996) combined data from different Pacific salmon species and populations showing that larger smolts have higher survival rates than smaller ones. For example, Koenings et al (1993) reported a strong relationship between size and survival among sockeye (O. nerka) salmon populations, though they also found that northern populations had higher survival rates than southern ones. However, the relationship was not linear; above ∟100 mm there seemed to be no increase in survival rate and there was even some evidence of lower survival rates for the largest smolts.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] This correlation is also supported by work on hatcheryreared fish (e.g. [1][2][3][4][5][6] This correlation is also supported by work on hatcheryreared fish (e.g.…”
Section: Introductionmentioning
confidence: 60%